2014
DOI: 10.4274/tjh.2013.0098
|View full text |Cite
|
Sign up to set email alerts
|

The Association of HLA Class 1 and Class 2 Antigens with Multiple Myeloma in Iranian Patients

Abstract: Objective: Multiple myeloma (MM) is a B-cell malignancy characterized by the clonal proliferation of malignant plasma cells. According to results of some studies, it has been suggested that the HLA class 1 and 2 genes have susceptibility effects on MM. Studies of different populations have reported different HLA class 1 and 2 alleles that affect MM. In this study, we assessed the association of HLA class 1 and class 2 antigens with MM in Iranian patients. Materials and Methods: We performed a case-control geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In a previous study, the HLA-A*03 and HLA-B*18 alleles were shown to have significant susceptibility effects on MM in the Iranian population [32]. The 2 HLA class I/II SNPs (rs6457327, rs2647012) were identified to date as susceptibility loci for NHL subtypes and have largely been associated with FL [33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the HLA-A*03 and HLA-B*18 alleles were shown to have significant susceptibility effects on MM in the Iranian population [32]. The 2 HLA class I/II SNPs (rs6457327, rs2647012) were identified to date as susceptibility loci for NHL subtypes and have largely been associated with FL [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…HLA class I- and class II-restricted CD8+ and CD4+ T-cell responses are essential for the immune system to mount a successful anti-tumor immune defense or to remove infected [ 18 ]. In a previous study, the HLA-A*03 and HLA-B*18 alleles were shown to have significant susceptibility effects on MM in the Iranian population [ 32 ]. The 2 HLA class I/II SNPs (rs6457327, rs2647012) were identified to date as susceptibility loci for NHL subtypes and have largely been associated with FL [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%